Avaliação da onda b do eletrorretinograma na Athene cunicularia - Márcio Penha Morterá Rodrigues; Adalmir Morterá Dantas (2008)
PURPOSE: To evaluate b-wave of the electroretinogram of the burrowing owl (Athene cunicularia), differentiating the retinal electric reply in photopic and scotopic environment. METHODS: Transversal observational study was carried through, with the register of the full field electroretinogram of fourteen eyes; seven were stimulated in photopic environment and seven in scotopic environment using with white light according to the ISCEV protocol. RESULTS: The electrical responses of the retina of the species studied showed no statistically significant difference for the applied [...]